2019
DOI: 10.1039/c8sc05598j
|View full text |Cite
|
Sign up to set email alerts
|

Using sulfur bridge oxidation to control electronic coupling and photochemistry in covalent anthracene dimers

Abstract: For anthracene dimers bridged by a sulfur atom, modulating the sulfur oxidation state profoundly affects excited state behavior. The SO2-bridge supports long-lived states and photodimerization, while the S-bridge undergoes intersystem crossing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 83 publications
1
16
0
Order By: Relevance
“…S14 and S15 †). 25,26 The increase in interchromophoric interaction and CT character of excited states with the oxidation state of the linker is consistent with our previous ndings 23 and computational studies showing a similar decrease of the electronic screening effect of sulfur lone pairs from S, to SO and SO 2 -bridged dimers. 24 Before carrying out solid-state photophysical measurements, powder X-ray diffraction (pXRD) patterns of CBZ-S and CBZ-SO were collected in order to determine the crystallinity and phase of the bulk samples (Fig.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…S14 and S15 †). 25,26 The increase in interchromophoric interaction and CT character of excited states with the oxidation state of the linker is consistent with our previous ndings 23 and computational studies showing a similar decrease of the electronic screening effect of sulfur lone pairs from S, to SO and SO 2 -bridged dimers. 24 Before carrying out solid-state photophysical measurements, powder X-ray diffraction (pXRD) patterns of CBZ-S and CBZ-SO were collected in order to determine the crystallinity and phase of the bulk samples (Fig.…”
Section: Resultssupporting
confidence: 90%
“…We have also demonstrated that the oxidation state at the sulfur bridge of conjugated homodimers, such as naphthalene or anthracene, controls their photochemistry by promoting photodimerization or enhancing the nonradiative decay through a conical intersection. 25,26 The concept of tuning the electronics of a species by varying the sulfur oxidation state has since been applied to various molecular systems including oligomers, polymers and metal complexes. [27][28][29][30][31][32] In the bridged terthiophene compounds, the bridging sulfur lone pairs (n(S)) are low in energy compared to the p HOMO of terthiophene, and thus do not participate signicantly in the low-lying excited states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two PIA bands are attributed to the absorption of the singlet (S 1 ) state of DPA based on the previous report. 50,51 With time delay, these two S 1 absorption bands showed an increase within the first ∼20 ps, as revealed by single-wavelength dynamics probed at ∼375 and ∼580 nm (Fig. S4, ESI†), which should be caused by vibrational cooling and rotation of the two phenyl rings at 9,10-position of DPA in the S 1 state.…”
Section: Resultsmentioning
confidence: 87%
“…This concept of temporal uorescence evolution is based on photochemical behavior found in sulfur-bridged dianthracenes that is dependent on the oxidation state of the sulfur bridge. 55,56 The weakly emissive 9,9 0 -dianthryl sulfoxide (1a) eliminates the SO bridge upon photoirradiation to form the strongly blue emissive molecule 9,9 0 -bianthracene (1b) ( Fig. 1) either in solution, or in polymer host matrices with glass transition temperatures (T g ) below room temperature, such as poly(butylmethacrylate).…”
Section: Introductionmentioning
confidence: 99%